Hygienologic status of disposable paper and plastic cups - ΠΩΤΗΣ, Α.; ΧΑΡΙΣΗΣ, Φ.; ΠΑΠΑΝΑΣΤΑΣΙΟΥ, Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
A total of disposable cups were evaluated for their hygienic conditions by determining their coliform count and the total mesophile aerobic microbial flora (TMA). The data indicate that the examined disposable items are of good hygienic status as no presence of coliform was detected nor their TMA flora was found significant.